Livestock Economics - Ruhela, Archana (Oxford Book Company, 2012)
Livestock economics, or the application of economic methods to optimizing the decisions made by livestock producers, grew to prominence around the turn of the 20th century. It focused on maximizing the yield of livestocks while maintaining a good ecosystem. Throughout the last century, the discipline expanded and the current scope of the discipline is much broader. Livestock economics today includes a variety of applied areas, having considerable overlap with conventional economics today include